PEMBERDAYAAN KELOMPOK PKK MELALUI PELATIHAN PEMBUATAN DAN PENGEMASAN TELUR ASIN OVEN SEBAGAI OLEH-OLEH KHAS KABUPATEN SIDENRENG RAPPANG - Nurhidayah, Asma'ul Fitriana; Sari, Anggun Permata; Syamsuddin, Syamsuddin; Hasman, Hasman; Ningrum, Endah Murpi; Hasrin, Hasrin; Wulandari, Sri Helda; Yamin, Abdul Alim; Chadijah, St.; Az-zahra, Rahmadani; Fauzan, Ahmad; Putri, Wira Lestari; Warman, Aditya; Junaedi, Junaedi; Sudarsono, Sudarsono (Universitas Mataram, 2025)
Sidenreng Rappang Regency is one of the duck production centers in South Sulawesi Province. However, most duck eggs are still marketed in fresh form with limited innovation in processing and packaging. The traditional management of existing processed products generally results in low competitiveness. This condition highlights the importance of innovation in processing and packaging to optimize local potential and contribute to improving community welfare. The purpose of this program was to empower PKK women’s groups in Manisa Village by enhancing their skills in producing oven-salted eggs and product packaging. The activities were carried out using a participatory approach through three stages: socialization, technical training on salted egg processing with an oven, and packaging training. The implementation showed a significant increase in participants’ knowledge across all aspects. Pre-test and post-test results indicated that basic knowledge of salted egg production increased from 37% to 76%, production using the wet method from 38% to 77%, and the use of ovens and packaging rose from 25–30% to 79%. This twofold increase reflects the effectiveness of practice-based training, where participants not only understood the concepts but were also able to apply the skills independently. Participants were also able to practice using vacuum plastic and attaching labels. The participants' response was very positive, as seen from their enthusiasm in the discussion and hands-on practice